The concept of the superhero in Filipino films - Flores, Emil M. (2005)
This essay examines a number of Filipino superhero films (Captain Barbell, Darna and Lastikman) and how a uniquely American creation was "Filipinized," taking into account the cultural and social aspects of the Pinoy superhero as demonstrated in the films. For the first time in Filipino film history, three superhero films were included in the 2003 Metro Manila Film Festival. While the producers were most likely following the popular trend in Hollywood, the films Fantastic Man, Captain Barbell, and Gagamboy, still reflect the Filipino longing for a hero to look up to. All films were big box-office hits. Just as 9/11 gave rise to the popularity of fantasy and superhero films in Hollywood, societal ills and the 2004 elections have fanned the flames of fantasy heroics in Filipino commercial films. While the American heroes (e.g. Captain Marvel, Superman, and Wonder Woman) have heavily influenced the Filipino superheroes, several aspects of Filipino culture and society are still evident in the films. It is also noteworthy that the comic book industry that created the superheroes is now experiencing a severe drop in popularity. Thus, film is now the medium that showcases the superheroes. The movie versions of these heroes have a history in film that is almost as long as the comic book versions, and modern audiences are more familiar with the movies than the comics.